2018
DOI: 10.1007/s10266-018-0359-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan nanoparticle, QMix, and EDTA on TotalFill BC sealers’ dentinal tubule penetration: a confocal laser scanning microscopy study

Abstract: The aim of the present study was to compare the effect of chitosan nanoparticle, QMix, and 17% EDTA on the penetrability of a calcium silicate-based sealer into dentinal tubules using a confocal laser scanning microscope (CLSM). Sixty mandibular premolar teeth were selected and randomly divided into three groups (n = 20) before root canal preparation according to the solution used in the final rinse protocol: chitosan, QMix, and EDTA groups. Twenty teeth of each group were filled with a TotalFill BC sealers' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…In the present study, the percentage of the sealer penetration in the 4 mm sections was greater than that in the 2 mm sections for all except the MDA group. The difference between apical and coronal sections has also been noted in previous studies [5,7,38]. One possible explanation for this difference is the decreased density and diameter of dentinal tubules in the apical root dentin, with some areas completely devoid of tubules [29,39].…”
supporting
confidence: 69%
“…In the present study, the percentage of the sealer penetration in the 4 mm sections was greater than that in the 2 mm sections for all except the MDA group. The difference between apical and coronal sections has also been noted in previous studies [5,7,38]. One possible explanation for this difference is the decreased density and diameter of dentinal tubules in the apical root dentin, with some areas completely devoid of tubules [29,39].…”
supporting
confidence: 69%
“…In contrast, 17% EDTA has no detergent in its composition and presents high surface tension and low permeability, which limits its chelating effect 33 . Interestingly, other studies showed that 17% EDTA and QMiX promoted similar sealer penetration 10,30,31 . www.nature.com/scientificreports www.nature.com/scientificreports/ Overall, the efficacy of the final irrigation protocols for debris/smear layer removal and sealer penetration decreased from the coronal to the apical thirds.…”
Section: Groupsmentioning
confidence: 90%
“…The effect of final irrigation with QMiX on tubular dentin sealer penetration was compared with 17% EDTA in previous studies 10,30,31 . However, to our knowledge, this is the first study to report the effects of PUI with QMiX on tubular dentin sealer penetration.…”
Section: Groupsmentioning
confidence: 99%
“…In dentistry, CH has shown antibiofilm (8) and chelating effects (7)(8)(9)(10). Its ability to remove the smear layer, similar to that of 17% EDTA and of calcium hydroxide intracanal medicament, has been confirmed by previous studies (6,7,(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 65%
“…Acetic acid (AA) can remove dentin calcium ions, favoring smear layer removal, but it can also reach the inorganic structure of dentin, causing subsequent erosion and changes in dentin microhardness (6). In order to obtain a chelating effect without harming the dentin content or periapical tissues, other solutions have been proposed and tested, such as chitosan (CH) (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%